Management of Sanggar Intan Keratuan Darah Putih as a Local Cultural Arts Institution in Kuripan Village, South Lampung Regency - Mustika Wulandari; Malarsih (Jurnal Ragam Pengabdian, 2026)
Rapid globalization and social change pose challenges to the sustainability of local arts and cultural traditions, particularly within indigenous communities that uphold ancestral values. These conditions require cultural institutions that are able to adapt while maintaining cultural continuity. Sanggar Intan Keratuan Darah Putih, located in Kuripan Village, South Lampung Regency, is a local arts and cultural institution rooted in the customary system of the Keratuan Darah Putih and plays an important role in preserving traditional Lampung dance. This study aims to describe and analyze the management of Sanggar Intan as a local arts and cultural institution. The research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, supported by source and technique triangulation. The findings show that Sanggar Intan is managed collectively through a community-based approach involving customary leaders, dance instructors, and the local community. Program planning and implementation align with customary preservation needs and community social dynamics, while group-based learning using demonstration and direct practice effectively transmits dance knowledge and cultural values. Sanggar Intan functions as a center for cultural preservation, a non-formal educational institution, and a medium for strengthening the cultural identity of the Keratuan Darah Putih community, despite ongoing challenges related to documentation and regeneration.